PENGEMBANGAN E-MODUL BERBASIS MODEL PEMBELAJARAN SELF DIRECTE LEARNING PADA MATA PELAJARAN PENGELASAN - Ramadhan, Anugrah Agung; Jalinus, Nizwardi (Jurnal Pendidikan Teknologi Kejuruan, 2021)
This study aimed to produce an e-module based on a self-directed learning model that was valid, practical and effective and was able to help students learn independently and understand SMAW manual arc welding theory. This study is a Reset and Development (R&D) study which refers to the ADDIE instructional development model. ADDIE development procedures namely Analysis, Design, Develop, Implementation and Evaluation. The results of this Research and Development produced a valid learning e-module based on the evaluation of material expert validators who declared valid and the material expert validators who declared valid. The practicality of using e-module was known from the use of e-module that going well and the results of students and teachers responses from questionnaire statements were high practicality. The results of the effectiveness were known from the increase in the students' understanding of subject and the test results of the difference between pre-test and post-test results of the application of this e-module were quite effective category. Based on this study, a learning e-module for SMAW Manual Arc Welding based on the Self Directed Learning model had produced. this was valid, practical and effective for use in learning and can improve the theoretical understanding of SMAW Manual Arc Welding subject.